2019
DOI: 10.1016/j.jallcom.2018.09.280
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al and Y content on the oxidation resistance of CrAlYN protective coatings for high temperature applications: New insights about the Y role

Abstract: CrAlYN hard coatings with two different average Al contents: 16 at.% and 25 at.%, and Y concentration varying between 1.2 and 5.7 at.% were deposited by direct current reactive magnetron co-sputtering of mixed Cr-Al and Y targets on commercial M2 steel substrates. The samples were heated to 1000 ºC in air during 2 h to study their oxidation resistance and thermal stability. The Y content is critical and the coatings present different behaviour depending on the Al content. The best oxidation resistance and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…At this time, the growth rate of composite film was faster, as it was found in similar composite films [14]. However, with the increase of sputtering power of La-Ti target, it can be seen from figures 1(b)-(e) that the surface of composite films are granular island structure, the crack between particles were reduced, and the films are denser, it had special electronic layer structure and chemical activity with the rare earth element La, and it was easy to gather and enrich to the grain boundary [15]. It could form stable compounds with the impurity elements such as hydrogen and oxygen, which could inhibit the growth and coarsening of grain and increase the nucleation rate.…”
Section: Methodsmentioning
confidence: 83%
“…At this time, the growth rate of composite film was faster, as it was found in similar composite films [14]. However, with the increase of sputtering power of La-Ti target, it can be seen from figures 1(b)-(e) that the surface of composite films are granular island structure, the crack between particles were reduced, and the films are denser, it had special electronic layer structure and chemical activity with the rare earth element La, and it was easy to gather and enrich to the grain boundary [15]. It could form stable compounds with the impurity elements such as hydrogen and oxygen, which could inhibit the growth and coarsening of grain and increase the nucleation rate.…”
Section: Methodsmentioning
confidence: 83%
“…A further study of co-sputtered coatings containing Y showed that excellent oxidation behaviour was achieved with a Y content of 3.4 at.% for Cr-rich Cr 25.8 Al 15.3 Y 3.4 N 55.5 coatings, whereas for Al-rich coatings, a lower Y content of 2.6 at.% was the best with Al 24.9 Cr 18.1 Y 2.6 N 54.4 . It was also found that higher Y contents promote the hcp phase formation [112].…”
Section: Al-cr-y-nmentioning
confidence: 96%
“…In this regard, multicomponent and multilayer coatings have been studied; by producing CrAlN, TiCN, TiAlN, and TiCrAlN new coatings, a significant step has been taken toward the development of hard and corrosion‐resistant coatings 7‐10 . Addition of aluminum to transition metal nitrides has led to a new group of hard coatings improving oxidation and corrosion behavior, thermal stability, and their hardness 11‐16 . Triple nitride coatings on the Cr base can prevent oxygen diffusion into the coating by forming dense protective oxides like Cr 2 O 3 and Al 2 O 3 , improving the corrosion properties of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…7-10 Addition of aluminum to transition metal nitrides has led to a new group of hard coatings improving oxidation and corrosion behavior, thermal stability, and their hardness. [11][12][13][14][15][16] Triple nitride coatings on the Cr base can prevent oxygen diffusion into the coating by forming dense protective oxides like Cr 2 O 3 and Al 2 O 3 , improving the corrosion properties of the coating. Also, chrome oxide layers are denser than titanium oxide layers, so nitride coatings on the chromium base can have a higher corrosion resistance.…”
mentioning
confidence: 99%